Evaluation of Aspergillus niger as a Biocontrol Agent in the Insect Pest Management of Red Cotton Bug, Dysdercus koenigii (Heteroptera: Pyrrhocoridae) - Kumar, D.; Kumari, S.; Verma, D. (Journal of Scientific Research, 2019)
The present work evaluates the efficacy of Aspergillus niger as a biocontrol agent against Dysdercus koenigii. Three concentrations (C1:1 × 104, C2:1 × 105 and C3:1 × 106 spores/mL respectively) were applied topically to the arthrodial membrane of adult insects and virulence of the fungi in terms of mortality was obtained, which was highest (66.66%) after 96 h post infection with 1 × 106 spores/mL. Its effect on cellular immune response was investigated. The decline in hemocyte count was highest in C3 group treated, i.e. 6992.66±216.34, followed by other groups. Differential hemocyte counts showed that granulocytes and plasmatocytes were the most affected hemocytes with count 26.33±0.66, 24±1.15 respectively in “C3” treated group in comparison to control, 33.66±2.07, 39.66±0.88 respectively. The humoral response was also studied by assessing the activity of four important antioxidant enzymes (superoxide dismutase, catalase, cytochrome p450 and glutathione-S-transferase) and lipid peroxidation that showed significant changes. Based on mortality test we can say that even the sub-lethal concentration can pose significant threat on insect pest. Our results further revealed that Aspergillus niger compromises the immunological parameters of insects and help us understand the underlying mechanism of insect response towards pathogens.